Fertilizer and Lime Impacts on Edaphic Mesofauna in a Southern Brazil Loblolly Pine System - de Albuquerque, Carla Gomes (Scientia Agraria, 2024)
Mesofauna play an important role in nutrient biocycling, but little attention has been given to fertilizer and lime impacts on forest floor and soil populations. The aim of this study was to evaluate the effect of fertilization and liming on edaphic mesofauna in a Pinus taeda L. system (Paraná State, Brazil). Lime and fertilizer were applied over litter in a six-year-old P. taeda system using three treatments: complete fertilization (N, P, K, Zn, Cu, B, Mo, and limestone), complete fertilization without lime, and a control. Four years later, winter and summer samples were collected from soil (0-5 cm) and litter for mesofauna and chemical properties. Results confirmed the importance of litter as a niche for mesofauna (94 % of total mesofauna; 286,627 individuals·m-2) compared to control soil (6 % of total mesofauna; 17,833 individuals·m-2). Seasonality was an important factor, with summer populations (135,000 individuals·m-²) being 3-fold higher than winter (42,000 individuals·m-2). Complete fertilization and fertilization without lime increased Oribatid mites in summer litter but decreased Collembola Arthropleona. In the summer, the mesofauna population in soil was lower under complete fertilization. Thus, fertilization and lime applications to P. taeda systems can change edaphic mesofauna in soil and litter.